Response of Chili Pepper (Capsicum spp.) Cultivars Cultivated in Benin to Salt Stress at Germination Stage - GANDONOU, GBOSSÈGNON CHRISTOPHE BERNARD; KPINKOUN, Julien; ZANKLAN, Ahissou Séraphin; MONTCHO, David (My University, 2018)
Aims: In this study, salt resistance level of six chili (Capsicum spp.) cultivars including five local cultivars (Adologbo, Gbatakin, Pili-pili, Gbatakin d’Agbédranfo, TPS0251) and one imported variety (Démon) grown in Benin was evaluated at the germination stage. Study Design: The experiment was laid out as a completely randomized design with four replications. Original Research Article Place and Duration of Study: The experiment was carried out in the Laboratory of Plant Physiologyand Abiotic Stresses Study of University of Abomey-Calavi, Republic of Benin from September through October, 2016. Methodology: Seeds were submitted to treatment with five NaCl concentrations (0; 30; 60; 90 and 120 mM NaCl) in petri dishes.Seed germination was checked every day during sixteen days incubation period. Four replicates of 40 seeds each were used. Results: From day 2 to day 16, NaCl delayed seed germination rate proportionately to NaCl concentration except for cultivars TPS0251 and Démon. At the end of the 16 days, NaCl stress effects on seed germination of cultivars were significantly variable. No significant reduction was observed for cultivars Démon and TPS0251 whereas a significant decrease was observed for the four other cultivars with a significant difference among them. The average reduction due to NaCl stress was lower for cultivars Démon (0%) and TPS0251 (4.31%) and higher for cultivar Pili-pili (63.61%). Salt Tolerance Index was significantly variable according to the cultivar with the highest values for cultivar Démon (1.227) and TPS0251 (1.127) and the weakest values for cultivars Pili-pili (0.374) and Gbatakin d’Agbédranfo (0.46). Conclusion: NaCl stress delayed seed germination and reduced the rate of final germination. Salt Tolerance Index was variable among the six cultivars: cultivars Démon and TPS0251 appeared to be the most salt resistant whereas Pili-pili and Gbatakin d’Agbédranfo appeared as the most salt sensitive at germination stage. For the first time, we demonstrated a variability of relative salinity resistance among local chili pepper cultivars at germination stage.
Keywords: Capsicum spp.; cultivars; germination; salt tolerance index; salt-resistance